Spore morphology and ultrastructure in species of salvinia from Southern South America - Gardenal, Paula (2008)
The morphology and ultrastructure of megaspores, microspores, and massulae of Salvinia Séguier 1785 species from Argentina, Bolivia, southern Brazil, Chile, Paraguay, and Uruguay have been analyzed. The analyses were performed using light microscopy, stereo microscopy, scanning electron microscopy, and transmission electron microscopy. The taxa studied were Salvinia auriculata Aublet 1775, Salvinia biloba Raddi 1825, and Salvinia minima Baker 1886. The spores of Salvinia biloba are described and illustrated here for the first time. The spores of Salvinia adnata Desvaux 1827were not described here because all the specimens analyzed had megasporangia and microsporangia which had not developed, or were aborted. The megaspores in all the species analyzed are trilete, 224–402 µm in polar diameter and 179–378 µm in equatorial diameter, with a circular outline, an irregular margin in polar view, and are ovoid in equatorial view. The surface is ridged and perforated and the sporoderm in cross section comprises a compact, two-layered exospore and a thick lacunose epispore which is projected proximally. The apertural area has unique characteristics in each species. The microspores are enclosed in spheroidal to elliptical massulae 145–240 µm in diameter. The individual microspores are trilete, rugulate, 15–36 µm in diameter, and spheroidal. In cross section, the exospore is two-layered. Both types of spores produced by the species analyzed exhibit little interspecific and intraspecific variability. Differences in general shape and proximal characteristics were found in megaspores at the species level. According to these, and previous, results Salvinia is a genus with stable palynological characteristics, all of them related to its adaptation to the aquatic environment.